تأثير مخاطر إستخدام تكنولوجيا المعلومات على جودة المراجعة-دراسة ميدانية- - أحمد, حريز عبد القادر; عماره, مسعي محمد; أحمد, بوته; عبد الحميد, طويل (University of eloued جامعة الوادي, 2019)
"الملخص: جاءت هذه الدراسة لمعالجة الإشكالية التالية: ما مدي تأثير مخاطر استخدام تكنولوجيا المعلومات على جودة المراجعة؟ لأن تكنولوجيا المعلومات أصبحت تستخدم في كل المجالات بكل مكوناتها وهذا لما تحققه من سرعة ودقة في الأداء. ويهدف البحث إلى دراسة المراجعة في ظل تكنولوجيا المعلومات وبيان إجراءاتها وأساليبها ومخاطر الناجمة عنها ولتحقيق هذا الهدف، قمنا بتقديم إطار نظري لموضوع الدراسة وثانيهما ميداني أو تطبيقي تمثل في إجراء دراسة ميدانية عن طريق استبيان، وهذا لمعرفة مدى تأثير مخاطر تكنولوجيا المعلومات على أداء المراجع الخارجي وجودة المراجعة وذلك بالاعتماد على المنهج الوصفي التحليلي . وقد خلصت الدراسة إلى مجموعة من النتائج أهمها: وجود اثر لمخاطر استخدام تكنولوجيا المعلومات على جودة المراجعة وتعتبر المخاطر المتعلقة بالأشخاص هي الاكثر تأثيرا، كما أن استخدام تكنولوجيا المعلومات أدى إلى تحسين إجراءات وأساليب المراجعة الخارجية، بالإضافة إلى أنها مكنت المراجع بالاستفادة من إمكانيات تنفيذ هذه الأعمال بسرعة وبدقة أكبر، كما أنها سهلت للمراجع عملية المراجعة والتأكد من صحة العمليات وبتكلفة وجهد أقل، ومع ذلك لابد أن تكون لدى المراجع المحاسبي مهارات متخصصة وكفاءة عالية يمكن اكتسابها من خلال المعرفة العلمية ودورات التدريبية لتمكن من التعامل مع هذه التكنولوجيا والحد من تلك المخاطر. الكلمات المفتاحية: تكنولوجيا المعلومات - مخاطر - جودة المراجعة. ""Abstract: This study came to answer the following question : to what extent does the risk of using information technology affects the quality of audit? since information technology is now used in all fields with all its components. and this is due mainly to its speed and precision in performance And this research aims at studying the review using information technology and pointing out its achievements ,manners and dangers. To reach this goal ,we presented a theoretical frame and a practical one to this study. the practical aim consists of a survey so as to know the extent of information technology influence on the performance of the external reviewer and the quality of reviewing depending on a descriptive and analytical way. This study came to a conclusion of findings, among which: is the Impact of IT risk on audit quality, and the risks related to persons are the most influential on the quality of work of the external auditor, Also use IT has led to the improvement of tasks and manners of the external review, in addition to the fact the at it allowed the reviewer to execute these actions quickly and precisely .moreover, it made the process of reviewing easier for the reviewer ,also ,it facilitated ensuring the operations with less energy and cost .beside that ,the accountant reviewer should have specialized skills and high competence which can le possessed through scientific knowledge and training courses which enable the reviewer to deal with this technology And reduce those risks. Key words : information technology – Risks - the quality of reviewing "
مذكرة ماستر محاسبة
Keywords: تكنولوجيا المعلومات - مخاطر - جودة المراجعة.; information technology – Risks - the quality of reviewing